A Novel Algorithm for Detecting Microsatellite Instability Based on Next-Generation Sequencing Data - Li, Shijun; Wang, Bo; Chang, Miaomiao; Hou, Rui; Tian, Geng; Tong, Ling (Frontiers in Oncology, 2022)
Objectives: Microsatellite instability (MSI) is the condition of genetic hypermutability caused by spontaneous acquisition or loss of nucleotides during the DNA replication. MSI has been discovered to be a useful immunotherapy biomarker clinically. The main DNA-based method for MSI detection is polymerase chain reaction (PCR) amplification and fragment length analysis, which are costly and laborious. Thus, we developed a novel method to detect MSI based on next generation sequencing (NGS) data. Methods: We chose 6 markers of MSI. After alignment and reads counting, a histogram was plotted showing the counts of different lengths for each marker. We then designed an algorithm to discover peaks in the generated histograms so that the peak numbers discovered in NGS data resembled that in PCR-based method. Results: We selected 9 samples as the training dataset, 101 samples for validation and 68 samples as the test dataset from Chifeng Municipal Hospital, Inner Mongolia, China. The NGS-based method achieved 100% accuracy for the validation dataset and 98.53% accuracy for the test dataset, in which only one false positive was detected. Conclusions: Accurate MSI judgements were achieved using NGS data, which could provide comparable MSI detection with the gold standard, PCR-based methods.